2019
DOI: 10.1596/1813-9450-9019
|View full text |Cite
|
Sign up to set email alerts
|

Conflict, Household Victimization, and Welfare: Does the Perpetrator Matter?

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…Since we account for deprivations in health and education in a multidimensional poverty framework and find statistically significant correlations between conflict and multidimensional poverty, our findings speak to recent evidence on conflict in Nigeria being associated negatively with monetary poverty, with food insecurity (see e.g. Kaila and Azad, 2019) and with school enrolment (Bertoni et al, 2019). Lastly, our empirical findings on spatial conflict spillovers complement Alderdice (2023), as well as Idler and Tkacova (2023) elsewhere in this Special Issue, underscoring the importance of territoriality, place and space.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Since we account for deprivations in health and education in a multidimensional poverty framework and find statistically significant correlations between conflict and multidimensional poverty, our findings speak to recent evidence on conflict in Nigeria being associated negatively with monetary poverty, with food insecurity (see e.g. Kaila and Azad, 2019) and with school enrolment (Bertoni et al, 2019). Lastly, our empirical findings on spatial conflict spillovers complement Alderdice (2023), as well as Idler and Tkacova (2023) elsewhere in this Special Issue, underscoring the importance of territoriality, place and space.…”
Section: Introductionsupporting
confidence: 60%
“…To provide a background to various conflicts in Nigeria, Kaila and Azad (2019) and Nwankpa (2014) group these into three broad categories that vary by region and type of actors. First, militant groups have been operating in the oil-rich Niger Delta across several states, engaged in activities ranging from kidnapping and robbery to attacks on petroleum installations and attacks on state institutions.…”
Section: Dynamics and Actors Of Conflict Eventsmentioning
confidence: 99%
“…In addition, they found negative effects on the variety of foods a household consumed and the portion size of the meals. In a related article that focused on food insecurity, using the GHS panel data complemented with a 2017 phone survey, Kaila and Azad (2019) explored the effect of conflict victimization on consumption and food security noting heterogeneity in the effects of conflict. In particular, they found that conflicts involving Boko Haram had more severe negative effects on consumption and food security than conflicts involving the Fulani herdsmen or militant groups in the Niger Delta.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only Kaila and Azad (2019) consider the impact of conflict at the individual level. However, the endogenous nature of individual-level exposure to conflict could bias their estimated coefficients.…”
mentioning
confidence: 99%
“…In addition they find negative e↵ects on the variety of foods the household consumed and the portion size of the meals. In a related paper that focused on food insecurity, using the GHS panel data complemented with a 2017 phone survey, Kaila and Azad (2019) explored the e↵ect of conflict victimization on consumption and food security noting heterogeneity in the e↵ects of conflict. In particular they find that conflicts involving Boko Haram had more severe negative e↵ects on consumption and food security than conflicts involving the Fulani herdsmen or militant groups in the Niger Delta.…”
mentioning
confidence: 99%